2015
DOI: 10.1002/cctc.201500256
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Fe–Ni Alloy on a Ceria Support as a Noble‐Metal‐Free Catalyst for Hydrogen Production from Chemical Hydrogen Storage Materials

Abstract: The front cover artwork for Issue 08/2015 is provided by the research group of Division of Materials and Manufacturing Science, Graduate School of Engineering, Osaka University (Japan). The image shows hydrogen production from an aqueous solution of ammonia–borane (NH3–BH3, AB) by bimetallic Fe–Ni nanoparticles supported on CeO2. See the Full Paper itself at http://dx.doi.org/10.1002/cctc.201500101.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is generally accepted that the ratio of Ni and Fe components determines whether the addition of Fe has a promoting or suppressing effect. 33,34 The Ni−Fe bimetallic effect was investigated by changing the Fe/ (Ni+Fe) weight ratios. The Ni−Fe/SiO 2 bimetallic catalysts with different Fe/(Ni+Fe) weight ratios were prepared at a total metal loading of 5 wt %.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…It is generally accepted that the ratio of Ni and Fe components determines whether the addition of Fe has a promoting or suppressing effect. 33,34 The Ni−Fe bimetallic effect was investigated by changing the Fe/ (Ni+Fe) weight ratios. The Ni−Fe/SiO 2 bimetallic catalysts with different Fe/(Ni+Fe) weight ratios were prepared at a total metal loading of 5 wt %.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…H 2 released from AB can follow two different pathways, through pyrolysis under considerably high temperatures, yielding only 6.5 wt % hydrogen (1 equiv based on AB) or the hydrolysis of AB in the presence of suitable catalysts, producing 19.6 wt % hydrogen (3 equiv based on AB) under mild reaction conditions through eq 1. 7 + → + +…”
Section: Introductionmentioning
confidence: 99%
“…This above conclusion, especially the role of amorphous metal NPs in the catalysis, was also testified by the reported amorphous Fe-based NPs having excellent catalytic activity. 16,20 To further lower the cost of monometallic Co catalysts, other much less expensive metals Cu, Fe, and Ni were used to partially replace Co to construct bimetallic catalysts CuCo/ MIL-101-1-U, FeCo/MIL-101-1-U, and NiCo/MIL-101-1-U, and their catalytic performance was studied. The results showed that the three bimetallic catalysts and monometallic Co/MIL-101-1-U had the similar activities (Figure 5), indicating that the present bimetallic strategy was effective for further lowering the cost of Co catalysts and meantime their activities were maintained.…”
Section: Resultsmentioning
confidence: 99%